Poly(Lactic Acid)/Tio2 Nanocomposites as Alternative Biocidal and Antifungal Materials - Zapata-Ramirez, P; Canales-Arévalo, D (Elsevier Ltd, 2015)
Abstract Poly(lactic acid) (PLA) composites with titanium oxide (TiO2) ~ 10-nm nanoparticles were produced by the melting process and their main properties were evaluated. The nanoparticles are homogeneously dispersed in the matrix with a low degree of agglomeration, as seen by transmission electron microscopy (TEM). The crystallinity temperature increased ~ 12% when 5 wt.% of TiO2 was added, showing that the nanoparticles acted as nucleating agents this trend was confirmed by optical images. The elastic modulus increased ~ 54% compared to neat PLA at 5 wt.% of nanoparticles. Despite these improvements, PLA/TiO2 nanocomposites showed lower shear viscosity than neat PLA, possibly reflecting degradation of the polymer due to the particles. Regarding biocidal properties, after 2 h of contact the PLA/TiO2 composites with 8 wt.% TiO2 showed a reduction of Escherichia coli colonies of ~ 82% under no UVA irradiation compared to pure PLA. This biocidal characteristic can be increased under UVA irradiation, with nanocomposites containing 8 wt.% TiO2 killing 94% of the bacteria. The PLA/TiO2 nanocomposites with 8 wt.% were also 99.99% effective against Aspergillus fumigatus under the UVA irradiation. © 2015 Elsevier B.V.